Comprehensive Transcriptome Analysis of Patients With Keratoconus Highlights the Regulation of Immune Responses and Inflammatory Processes - Sun, Xiao; Zhang, Hao; Shan, Mengyuan; Dong, Yi; Zhang, Lin; Chen, Luxia; Wang, Yan (Frontiers in Genetics, 2022)
Keratoconus (KTCN), characterized by the steeper curvature of the cornea and the thinner central corneal thickness, was a degenerative corneal ectasia with ambiguous etiology and mechanism. We aim to reveal underlying pathological mechanisms of KTCN by multi-level transcriptomic, integrative omics analyses. We performed RNA-sequencing on corneal samples from seven patients and seven control donors, as well as peripheral matched blood samples from three of the patients and three control donors. After RNA extraction, library construction, and sequencing, differentially expressed genes and splicing events were identified, followed by over-representation analysis. In total, 547 differential expressed genes were identified in KTCN corneal samples, which were mainly enriched in immune responses and inflammatory processes. WGCNA module analysis, the transcriptomic analysis of peripheral blood samples and integrated analysis of multiple omics data confirmed the involvement of immune and inflammatory factors. Besides, 190 and 1163 aberrant splicing events were identified by rMATS combined with CASH methods in cornea and blood samples with KCTN. In conclusion, this comprehensive transcriptome analysis of KTCN patients based on patients’ tissue and blood samples uncovered significant association between immune-inflammatory genes and pathways with KCTN, highlighting the contribution of the perturbed immune signaling to the pathogenesis of KCTN. Our study suggested the importance of measures to control inflammation in the treatment of KCTN.